A New Data Landscape: IR's Role in Academic Analytics. Issue 185 (2nd February 2021) - Hawkins, Christie; Bailey, Lucy E.
Abstract: The increasing volume of information and the intense pace of its circulation are changing the ways universities access, use, analyze, and provide data. Many have championed the use of large‐scale databases to track student admissions and retention, faculty productivity, student wellness, and other phenomena that shape our understandings of higher education. These changes have had major effects on analytics as well. This chapter outlines how analytics can assist the academic side of colleges and universities to best serve all academic stakeholders, including administrators, faculty, and staff. It also addresses the evolving roles of Institutional Research Offices in helping set institutional strategies, collaborating across university offices to develop analytics, and cultivating an institutional culture of informed decision making. IR Offices should consider various facets of the process of collecting, analyzing, and communicating information to serve academic departments. One priority is determining which software, tools, and approaches best align with institutional priorities and needs. Another is creating specific analytics that serve the academic missions of and strategic planning for the institution and representing data in accessible ways to serve academic administration's diverse purposes and roles. Finally, cultivating buy‐in and support from administration and other stakeholders is essential. IR offices can be instrumental in fostering academic colleagues' use, interpretation, and valuing of data and in developing collaborative relationships with academic leadership, colleges and departments. The new data analytics landscape requires expanding the roles and institutional reach of IR offices, thus creating opportunities for IR involvement in strategic planning and vision at high levels of their institutions.